Effects of Time of Second Nitrogen Application on Growth and Development of Rice Plants - Othman, Sariam (1987)
Pot and field experiments were conducted to study the effect of different times of second nitrogen (N) application on growth, yield, protein content of grain and milling quality of rice (Oryza sativa L variety Seberang). Second N application was carried out at three-day intervals from 39 to 78 and 39 to 81 days after transplanting in pot and field experiments, respectively. Experimental design used was a randomized complete block design with treatments replicated three times. In the pot experiment, significantly higher yields were obtained from second N application made from late vegetative (39 days after transplanting) to late primary rachis branch differentiating stage (48 days after transplanting) and at middle stage of spike let differentiation (57 days after transplanting). Time of second N application had no significant effect on grain yield in the field but second N applied at panicle initiation stage (45 days after transplanting) resulted in the highest grain yield. In the field, second N application made from late vegetative to late primary rachis branch differentiating stage and from extine formation stage (66 days after transplanting) onwards significantly increased panicle number and percentage of filled grains, respectively.